2011
DOI: 10.1371/journal.pone.0021623
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Three-Player Quantum Games in an EPR Type Setup

Abstract: We use the formalism of Clifford Geometric Algebra (GA) to develop an analysis of quantum versions of three-player non-cooperative games. The quantum games we explore are played in an Einstein-Podolsky-Rosen (EPR) type setting. In this setting, the players' strategy sets remain identical to the ones in the mixed-strategy version of the classical game that is obtained as a proper subset of the corresponding quantum game. Using GA we investigate the outcome of a realization of the game by players sharing GHZ sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 61 publications
(108 reference statements)
4
23
0
Order By: Relevance
“…These general results thus subsume previous analyses for two-player and three-player games in an EPR setting [49], [50].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These general results thus subsume previous analyses for two-player and three-player games in an EPR setting [49], [50].…”
Section: Discussionsupporting
confidence: 83%
“…Following [49], [50], we can then form the bivectors , which are non-commuting for , with but if we have . We also have the trivector.finding and furthermore, that commutes with each vector , thus acting in a similar fashion to the unit imaginary .…”
Section: Introductionmentioning
confidence: 99%
“…Classically defined games have been analyzed and it has been found that a quantum team has an advantage over any classical team [81]. Quantum games have also been analyzed by using geometric algebra [82]–[84], and they have been implemented using quantum computers [85][88]. For further background on quantum games, we refer to [89], [90].…”
Section: Introductionmentioning
confidence: 99%
“…Later, Iqbal et al [26] studied evolutionarily stable strategies in quantum games and Kay et al [27] presented an evolutionary quantum game. Other related studies have also been performed [28][29][30][31][32]. For further background on quantum games, see [33,34].…”
Section: Introductionmentioning
confidence: 99%